Aftermath of ICT Literacy on Prevalence of Malaria Parasite among HIV/AIDS Patients - N, Vivian; Oye, Nathaniel (International Journal of Public Health Science (IJPHS), 2012)
The role of ICT in the prevention and mitigation efforts for HIV/AIDS cannot be over emphasized. The greatest advantage of ICTs is that they can reach out to remotest areas.  So through the innovative use of ICTs youths and even adults can have access to HIV/AIDS programmes that can meet their needs. The paper focuses on the aftermath of ICT literacy on malaria parasite among HIV/AIDS patients. Therefore, to achieve positive results in the fight against HIV/AIDS ICTs should be taken on board. HIV/AIDS information should be found everywhere i.e. radio, cell phone, TV and internet. ICTs make HIV/AIDS information easily accessible, confidential and user friendly. The study has shown the possibility of co-infection of HIV positive or negative patients with malaria and HBsAg. This phenomenon could increase the severity of HIV infection and facilitate the progression of HIV to AIDS. The practices of universal screening of blood should be implemented to improve the safety of blood supply so as to reduce the risk of Hepatitis B Virus (HBV) and Human Immunodeficiency Virus (HIV).  More malaria enlightenment programmes by the Local Community, the government and nongovernmental organization should be implemented.DOI: http://dx.doi.org/10.11591/ijphs.v1i1.539